1998
DOI: 10.1007/s002669900175
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Median Part of the Septum Depressor Muscle in Aesthetic Surgery

Abstract: When a person smiles and talks, everyone in his or her own specific way, it can be noticed that the tip of the nose drops and the upper lip shortens, making the nasolabial angle more acute. The importance of the upper lip in the dynamics of the nose makes necessary a more detailed study of the morphology and anatomical relations of the median part of the nasal septum depressor muscle, contributing in this way to new techniques in plastic surgery. The authors proposed to study the anatomy of the nasal septum de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…The DSN inserted into the anterior nasal septum, then the footplates of the medial crura, and continued into the membranous septum. In patients with a thicker skin envelope, it was possible to show a distinct continuation of DSN into the deep median SMAS, thus confirming the original observations of Pitanguy 14 and de Souza Pinto et al 13 Due to the large cross-sectional diameter of the muscle and its broad insertion into the mobile columella and alar cartilages, its role as a depressor of the nasal tip was easily confirmed.…”
Section: Depressor Septi Nasalissupporting
confidence: 84%
See 1 more Smart Citation
“…The DSN inserted into the anterior nasal septum, then the footplates of the medial crura, and continued into the membranous septum. In patients with a thicker skin envelope, it was possible to show a distinct continuation of DSN into the deep median SMAS, thus confirming the original observations of Pitanguy 14 and de Souza Pinto et al 13 Due to the large cross-sectional diameter of the muscle and its broad insertion into the mobile columella and alar cartilages, its role as a depressor of the nasal tip was easily confirmed.…”
Section: Depressor Septi Nasalissupporting
confidence: 84%
“…11,12 It is often considered a part of the myrtiformis or a small attachment of the orbicularis oris. In 1998, de Souza Pinto et al 13 On the basis of our dissections, we found distinct paired DSN muscles originating from the maxilla directly above the central incisor in 14 of 15 cadavers ( Figure 6). In 1 case, the muscle appeared to originate from the orbicularis oris rather than the maxilla.…”
Section: Depressor Septi Nasalismentioning
confidence: 53%
“…Basically, it is widely accepted that there are five distinct layers above the cartilaginous and bony nasal structures [9,10]. There is also a relationship between the ligament of Pitanguy and a few muscle groups such as the median part of the septum depressor muscle, which is located mostly in the lower third and the lower third of the middle third [11]. The nasalis muscle is another two-belly muscle in this complex.…”
Section: Anatomymentioning
confidence: 99%
“…Among these structures are the depressor septi nasi muscles (Fig. 1), which are small, paired muscles located on either side of the caudal septum [2][3][4][5]. Three variations of the depressor septi nasi muscle have been described: type I inserts fully into the orbicularis oris (the most common type), type II inserts into the periosteum and incompletely into the orbicularis oris, and type III is rudimentary or does not exist at all [6].…”
Section: Introductionmentioning
confidence: 99%